Proto-languages and proto-Sprachgefühl - Matisoff, James A. (2024)
This is a somewhat cut and edited version of the paper presented at the XIVth International Conference on Sino-Tibetan Languages and Linguistics, University of Florida (Gainesville), October 29-31, 1981. Since several footnotes were excised at the beginning of the paper, it will be noticed that the numbering of the notes jumps from 9 to 18. For this I beg the reader's indulgence - it seemed preferable to re¬numbering all the rest of the 157 notes: I would like to thank Paul K. Benedict, Nicholas C. Bodman, David Bradley, Axel SchUssler, and David Strecker for their valuable comments and criticisms, several of which have been incorporated into the notes and addenda.